CONSUMER PROTECTION FOR ONLINE BANKING SCAMS VIA E-MAIL IN MALAYSIA (UUM Journal of Legal Studies, 2012)
The new advancement in technology both hard and soft is creating new opportunities for cyber criminals. It is an effective tool for going against the law. In the economic sector, the number of Malaysians opting for online banking to do transaction is increasing. There are 9.8 million online banking account holders in Malaysia. However, cases of online banking scams in Malaysia have been increasing since such first case was registered in 2005. Statistics from Financial Mediation Bureau showed that the number of cases had increased. Therefore, the objectives of this paper are to identify cyber scams via email in online banking business model and to examine consumer protection of online banking scams in Malaysia.Keywords: Online banking scam, email scam, phishing website